Use of malt bagasse as na adsorbent for the removal of the methylene blue dye (Research, Society and Development, 2020)
Malt bagasse is a viable alternative to be used as an adsorbent, as it is produced in large quantities during the beer production process. The present study aimed to evaluate the percentage of removal of the methylene blue content in synthetic effluent using malt bagasse as an adsorbent. The material was characterized by particle size analysis, X-ray diffraction (XRD), infrared spectroscopy with Fourier transform (FT-IR), and thermogravimetric analysis (TGA). The experiments were carried out based on a 2³ experimental plan with three replicates at the central point. There were three independent variables: methylene blue concentration (40, 60, and 80 mg / L), pH (6, 7, and 8) and time (4, 5, and 6 hours). The best conditions were obtained through the treatment of experimental data in the software Statistica 13.0. The bagasse had a removal percentage of approximately 94% for the highest concentration level (80 mg / L), lowest pH level (6), and the shortest time (4 hours). Thus, malt bagasse is efficient in removing methylene blue in synthetic effluent, so it is an alternative because it is also economically viable.